The Effect Of Overhand Passing Training Using (Wall Bounce) On The Accuracy Of Overhand Passing Skills In Volleyball - Sari, Felinda; Armanjaya, Satria; Ramadhan, Ziko Fajar; Renaldi, Renaldi; Iksan, Khoiril (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2025)
Objectives. The purpose of this study is to analyze the effect of overhand passing training using a wall target (wall bounce) on improving overhand passing skills in volleyball. Materials and Methods: This study employed an experimental method. Data were collected through pre-test and post-test. The sample consisted of undergraduate students from the Physical Education program at Universitas Aisyah Pringsewu, selected randomly. The overhand passing accuracy test served as the research instrument. Results: The average results of the study showed that the pre-test accuracy score for overhand passing was 26.25, while the post-test average score increased to 33.7. In the pre-test, the calculated t-value was 21.000, which is greater than the t-table value of 1.859. Similarly, in the post-test, the calculated t-value was 18.445, which also exceeded the t-table value of 1.859. These results indicate a significant effect. Therefore, it can be concluded that overhand passing training using a wall target has a significant impact on the accuracy of overhand passing skills in volleyball among undergraduate Physical Education students at Universitas Aisyah Pringsewu.